The Importance of Hyperthyroid Screening in Acute Decompensated Heart Failure with Persistent Tachycardia Despite Optimal Decongestion: A Case Report - Myrtha, Risalina; Wijayanto, Matthew Aldo; Prabowo, Nurhasan Agung (The Indonesian Heart Association, 2025)
In “The Importance of Hyperthyroid Screening in Acute Decompensated Heart Failure with Persistent Tachycardia Despite Optimal Decongestion: A Case Report” (Indonesian Journal of Cardiology, 43(3), 123-9. https://doi.org/10.30701/ijc.1328), there is an error noted. An error has been found in the PDF version of this article. The DOI printed in the PDF is incorrect. The correct DOI is https://doi.org/10.30701/ijc.1328. The error occurs only in the PDF; the DOI listed in the article metadata is already correct.The publisher apologizes for any inconvenience caused by this error.DOI of original article: https://doi.org/10.30701/ijc.1328